Pleiotropic QTLs affecting heading date/flowering time and quality traits in durum wheat - Roncallo, Pablo Federico (2018)
The QTL analyses are a powerful tool to dissect complex phenotypic traits. We conducted a study to map QTLs associated with heading date and flowering time by using a durum wheat RIL population obtained from the cross between the UC1113 line and the Kofa variety. This population was previously used to report QTLs for quality traits (grain color, carotenoids content , protein content and gluten strength).We perform new analyses by using heading date and flowering time data sets and were localized pleiotropic QTLs in three genomic regions associated with heading date/flowering time and quality.